Possible causes of methane release from the East Arctic seas shelf - O. A. Anisimov; Yu. G. Zaboikina; V. A. Kokorev; L. N. Yurganov (Лëд и снег, 2015)
We analyze data on methane concentration in the water and lower atmosphere over the shelf of the East Siberian Arctic Seas, which were obtained using marine, terrestrial, and satellite observations. Our study is targeted towards attribution of the enhanced concentrations of methane above the latitudinal-mean, which have been detected at selected locations of these seas. We compare two hypothesis, which attribute it to the effect of modern changes of the sub aquatic permafrost, and to geological factors (tectonics, presence of fault zones and paleo river beds in the study region). Our analysis showed that the methane concentration in sea water are directly related to the distance to the nearest fault zone or paleo river bed, where permafrost is absent and bottom sediments are perforated allowing methane to escape from the deep layers containing gas hydrates. This result indicate that the enhanced emission of methane, which was observed at selected locations of the shelf, is not related to the modern climate change. Earlier study, which was based on mathematical modeling, did not find intensive development of taliks as well as other processes that lead to increased gas permeability of the bottom sediments. Taken together, these results reject the hypothesis of methane catastrophe on the East Siberian Arctic Seas shelf over the foreseeable future.